A soft coral-derived compound, 11-epi-sinulariolide acetate suppresses inflammatory response and bone destruction in adjuvant-induced arthritis. - Yen-You Lin; Yen-Hsuan Jean; Hsin-Pai Lee; Wu-Fu Chen; Yu-Min Sun; Jui-Hsin Su; Yi Lu; Shi-Ying Huang; Han-Chun Hung; Ping-Jyun Sung; Jyh-Horng Sheu; Zhi-Hong Wen (PLoS ONE, 2013)
In recent years, a significant number of metabolites with potent anti-inflammatory properties have been discovered from marine organisms, and several of these compounds are now under clinical trials. In the present study, we isolated 11-epi-sinulariolide acetate (Ya-s11), a cembrane-type compound with anti-inflammatory effects, from the Formosa soft coral Sinularia querciformis. Preliminary screening revealed that Ya-s11 significantly inhibited the expression of the proinflammatory proteins induced nitric oxide synthase and cyclooxygenase-2 in lipopolysaccharide-stimulated murine macrophages. We also examined the therapeutic effects of Ya-s11 on adjuvant-induced arthritis (AIA) in female Lewis rats, which demonstrate features similar to human rheumatoid arthritis (RA). Animal experiments revealed that Ya-s11 (subcutaneously 9 mg/kg once every 2 days from day 7 to day 28 postimmunization) significantly inhibited AIA characteristics. Moreover, Ya-s11 also attenuated protein expression of cathepsin K, matrix metalloproteinases-9 (MMP-9), tartrate-resistant acid phosphatase (TRAP), and tumor necrosis factor-α (TNF-α) in ankle tissues of AIA-rats. Based on its attenuation of the expression of proinflammatory proteins and disease progression in AIA rats, the marine-derived compound Ya-s11 may serve as a useful therapeutic agent for the treatment of RA.